2016
DOI: 10.1002/mnfr.201500654
|View full text |Cite
|
Sign up to set email alerts
|

Fuzhuan tea consumption imparts hepatoprotective effects and alters intestinal microbiota in high saturated fat diet‐fed rats

Abstract: These data suggest that Fuzhuan tea protects against liver and adipose tissue stress induced by a high SAT diet and positively influences intestinal function. Further investigation of the molecular targets of Fuzhuan tea is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
51
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(55 citation statements)
references
References 36 publications
4
51
0
Order By: Relevance
“…It has been reported that the relative abundance of Lactobacillus spp. showed a threefold increase due to FBT intervention in high saturated fat diet‐fed rats . However, the increase in the relative abundance of Lactobacillus spp.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…It has been reported that the relative abundance of Lactobacillus spp. showed a threefold increase due to FBT intervention in high saturated fat diet‐fed rats . However, the increase in the relative abundance of Lactobacillus spp.…”
Section: Discussionmentioning
confidence: 98%
“…Furthermore, Lactobacillus johnsonii and another Lactobacillus sp. in high saturated fat diet‐fed rats could be enhanced by FBT intake . However, the potential role of gut microbiota modulated by KDC and FBT in the prevention of obesity is still not clearly understood.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, tea has exhibited the neuro-protective effect, in terms of protecting against age-related neuro-degenerative disorders, depression and regulating the circadian clock [184][185][186][187][188][189][190]. Moreover, tea could inhibit gastric ulcer and improve gastrointestinal function [191][192][193][194][195]. Besides, tea could modulate gut microbiota composition (increase beneficial microorganisms and decrease harmful microorganisms), which might be beneficial to those in the risk of obesity, metabolic syndrome, hyperlipidemia, and cardiovascular diseases [196][197][198][199][200][201][202].…”
Section: Other Health Functionsmentioning
confidence: 99%
“…Fuzhuan brick tea (FBT, also named Fu brick tea) is a fermented tea in the presence of a dominant fungi species named Eurotium cristatum, which is yellow-colored and is thus also called "golden flora" (" 金花") in Chinese 23 . Human consumption of FBT dated back to the 16 th century 24 , while recent pilot dietary interventions on humans in China have also shown that FBT consumption could improve metabolic disease conditions, which were summarized in Supplementary Table 1. FBT consumption or polysaccharides extracted from FBT were shown to reduce obesity, hyperlipidemia and arterial stiffening, as well as to improve metabolic syndrome in animals [25][26][27][28] . The water or ethanol extracts of FBT reduced obesity through normalizing gut microbiota in mice 25,29 .…”
Section: Introductionmentioning
confidence: 99%